Ultrasonic imaging contrast enhancement using modified dehaze image model. Issue 19 (1st September 2013) - Guo, Dequan; Liu, Paul; She, Yue; Yang, Hongyu; Liu, Dong
Abstract : In practical ultrasonic images, post‐processing that involves incoherent frame averaging such as persistence, spatial compounding and frequency compounding creates a layer of smoothed out electronic noise that is analogous to fog in photographic images. A novel approach to enhance ultrasound image contrast based on a modified dark channel model used to dehaze photographs is presented. Local minimum intensity is used to highlight image contrast, control influence of noise layer and improve detail resolution by different levels. The experimental results show that the proposed method has better performance over the existing methods in improving the quality of the ultrasonic image.